A Scaling Eect of Visual Force in Haptic Bilateral Control System - Jamaluddin, Muhammad Herman; Shimono, Tomoyuki; Motoi, Naoki (The Institute of Electrical Engineers of Japan (IEEJ), 2013)
This paper proposes a vision-based force controller for a haptic bilateral control system. According to the particular objects movement, a haptic bilateral system can be navigated in a specic direction by the proposed vision-based force controller. The generated force is treated as a disturbance in the bilateral control strategy. In the paper, the scaling effect which involves the distance between the object and the manipulator is considered as a key feature to be studied. The same magnication factor of vertical movement will be used for the horizontal displacement. The performance of this scaling eect produced by the visual force to the bilateral control system will be examined and analyzed through the actual experiments.